HSP90 inhibitors in the context of heat shock and the unfolded protein response: effects on a primary canine pulmonary adenocarcinoma cell line*. (3rd April 2017) - Graner, Arin N.; Hellwinkel, Justin E.; Lencioni, Alex M.; Madsen, Helen J.; Harland, Tessa A.; Marchando, Paul; Nguyen, Ger J.; Wang, Mary; Russell, Laura M.; Bemis, Lynne T.; Anchordoquy, Thomas J.; Graner, Michael W.
Abstract: Background: Agents targeting HSP90 and GRP94 are seldom tested in stressed contexts such as heat shock (HS) or the unfolded protein response (UPR). Tumor stress often activates HSPs and the UPR as pro-survival mechanisms. This begs the question of stress effects on chemotherapeutic efficacy, particularly with drugs targeting chaperones such as HSP90 or GRP94. We tested the utility of several HSP90 inhibitors, including PU-H71 (targeting GRP94), on a primary canine lung cancer line under HS/UPR stress compared to control conditions. Methods: We cultured canine bronchoalveolar adenocarcinoma cells that showed high endogenous HSP90 and GRP94 expression; these levels substantially increased upon HS or UPR induction. We treated cells with HSP90 inhibitors 17-DMAG, 17-AAG or PU-H71 under standard conditions, HS or UPR. Cell viability/survival was assayed. Antibody arrays measured intracellular signalling and apoptosis profiles. Results: HS and UPR had varying effects on cells treated with different HSP90 inhibitors; in particular, HS and UPR promoted resistance to inhibitors in short-term assays, but combinations of UPR stress and PU-H571 showed potent cytotoxic activity in longer-term assays. Array data indicated altered signalling pathways, with apoptotic and pro-survival implications. UPR induction + dual targeting of HSP90 and GRP94 swayed the balance toward apoptosis. Conclusion: Cellular stresses, endemic to tumors, or interventionally inducible, can deflect or enhance chemo-efficacy, particularly with chaperone-targeting drugs. Stress is likely not held accountable when testing new pharmacologics or assessing currently-used drugs. A better understanding of stress impacts on drug activities should be critical in improving therapeutic targeting and in discerning mechanisms of drug resistance.